2018
DOI: 10.30880/ijie.2018.10.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Computerized Maintenance Management System on a Cement Production Plant

Abstract: Computerized Maintenance Management System (CMMS) is a tool tailored to support maintenance business functions of production systems. Market available CMMS software programs seldom meet the needs of each organization's peculiar maintenance functions. Therefore, this work investigated the effects of CMMS on a cement production plant. The materials used included a Computer and Networking system and maintenance software. Preliminary study via interview among the relevant maintenance staff members of the plant was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Their orientation is more focused on the operational performance. Besides, the method of SMART system is able to identify the feedback context to monitor organizational performance and to improve performance measurement over the traditional action [11]. This model is often used by small and medium sized organizations to measure the performance of the organization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their orientation is more focused on the operational performance. Besides, the method of SMART system is able to identify the feedback context to monitor organizational performance and to improve performance measurement over the traditional action [11]. This model is often used by small and medium sized organizations to measure the performance of the organization.…”
mentioning
confidence: 99%
“…Therefore, this study will use the Smart system in developing SME performance measurement model. However, this method still lack of mechanism to identify key performance indicators, to determine the form act of measurement and also to integrate implicitly the concept of continuous improvement [11]. Thus, it needs the integration of other methods to cover the shortcomings of the SMART method to identify the key indicators.…”
mentioning
confidence: 99%
“…To optimize production, ensure high equipment reliability and utilization, it is necessary to run the machines at high efficiency without premature and preventable failure or breakdown which disrupts production and leads to economic loss. This sort of increase in reliability and machine utilization was demonstrated in Adetunji et al [16] as increase in cement production was recorded when computer maintenance management system became operational, leading to increase in revenue. Having made it known by Lv et al [17] that "the Kiln Head Temperature (KHT) is a key thermal variable to condition monitoring and stable control of the rotary kiln", they implemented a hybrid dynamic prediction framework to accurately predict the KHT chaotic time series in real-time and it was found that the implemented framework has the capability to capture dynamic evolution of KHT with respect to time.…”
mentioning
confidence: 86%
“…Some organisations consider using CMMS (Computerised Maintenance Management System) in order to manage the maintenance task and schedule. The impact of application of CMMS in organisation has been observed by [13]. The result of the research indicates that the application of CMMS can support OPEX, however in some cases it is expensive and unaffordable.…”
Section: Fig 1 -The Structure Of Operational Excellence As In [2]mentioning
confidence: 97%